Finance. - Phylaktis, Kate; Kaye, Geraldine (Reviews of United Kingdom statistical sources ;, 1987)
This volume reviews the publicly available sources of statistical information on finance, covering the UK monetary sector, banks, finance houses, building societies and other financial institutions. It also deals with pensions, life insurance, government statistics and professional and trade associations.